Design Of Coal Preparation Plants Using A 32k Microcomputer - M. J. Laurila (Society for Mining, Metallurgy & Exploration, 1982)
Utilizing data compiled from a drilling program and bulk samples taken from a coal reserve, flowsheet performance for a coal preparation plant can be calculated using a desktop computer. Sets of equations defining material balances involving coal preparation plant unit operations are employed to depict plant performance. Techniques are discussed for interpolating washability data and extrapolating size distributions and other critical data to expand on oftentimes limited sets of quality data to a useable data base from which projections can be made. Simulation of flowsheets can be done for a number of different conditions and configurations while still remaining in a limited working memory capacity of 32,000 bytes. Presented within this paper are several pertinent examples.